HRM practices and employee creative behavior of banking industry in Bangladesh: antecedent and outcome of employee retention - Siddika, Ayasha (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2023.